Integrative ATAC-seq and RNA-seq analyses of IPEC-J2 cells reveals porcine transcription and chromatin accessibility changes associated with Escherichia coli F18ac inhibited by Lactobacillus reuteri - Qin, Weiyun; Xie, Yunxiao; Ren, Zhanshi; Xu, Chao; Sun, Ming-an; Yin, Zongjun; Bao, Wenbin (Frontiers in Microbiology, 2023)
Escherichia coli (E. coli) is the main cause of postweaning diarrhea in pigs, leading to economic loss. As a probiotic, Lactobacillus reuteri (L. reuteri) has been used to inhibit E. coli in clinical applications; however, its integrative interactions with hosts remain unclear, especially in pigs. Here, we found that L. reuteri effectively inhibited E. coli F18ac adhering to porcine IPEC-J2 cells, and explored the genome-wide transcription and chromatin accessibility landscapes of IPEC-J2 cells by RNA-seq and ATAC-seq. The results showed that some key signal transduction pathways, such as PI3K-AKT and MAPK signaling pathways, were enriched in the differentially expressed genes (DEGs) between E. coli F18ac treatment with and without L. reuteri groups. However, we found less overlap between RNA-seq and ATAC-seq datasets; we speculated that this might be caused by histones modification through CHIP-qPCR detection. Furthermore, we identified the regulation of the actin cytoskeleton pathway and a number of candidate genes (ARHGEF12, EGFR, and DIAPH3) that might be associated with the inhibition of E. coli F18ac adherence to IPEC-J2 cells by L. reuteri. In conclusion, we provide a valuable dataset that can be used to seek potential porcine molecular markers of E. coli F18ac pathogenesis and L. reuteri antibacterial activity, and to guide the antibacterial application of L. reuteri.